2019
DOI: 10.1111/jam.14380
|View full text |Cite
|
Sign up to set email alerts
|

Generating amplicon reads for microbial community assessment with next‐generation sequencing

Abstract: Marker gene amplicon sequencing is often preferred over whole genome sequencing for microbial community characterization, due to its lower cost while still enabling assessment of uncultivable organisms. This technique involves many experimental steps, each of which can be a source of errors and bias. We present an up-to-date overview of the whole experimental pipeline, from sampling to sequencing reads, and give information allowing for informed choices at each step of both planning and execution of a microbia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 161 publications
0
50
0
Order By: Relevance
“…Several studies have shown that larger PCR cycle numbers cause chimera generation and interfere with bacterial community structure analysis 39 , 40 . Hence, minimizing the number of PCR cycles by optimizing the starting template conditions and concentrations is important 26 . However, in our situation, reducing the number of PCR cycles to less than 35 decreased the number of environmental DNA samples that were amplified.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that larger PCR cycle numbers cause chimera generation and interfere with bacterial community structure analysis 39 , 40 . Hence, minimizing the number of PCR cycles by optimizing the starting template conditions and concentrations is important 26 . However, in our situation, reducing the number of PCR cycles to less than 35 decreased the number of environmental DNA samples that were amplified.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of the microbial communities using modern genomic tools has enabled the detection of distinctive microorganisms that were not approachable by culture-based techniques. Gene amplification (using PCR) and sequencing techniques have proven exceptionally useful in evaluating the microbial community (Malik et al, 2008;Rani et al, 2008;Gołebiewski and Tretyn, 2020).…”
Section: Genomics and 16s Rrna For Bioremediationmentioning
confidence: 99%
“…Nonetheless, the application of these techniques is not free from difficulties, due to (among the others) the semiquantitative nature of data, the short DNA reads obtained by the most common HTS techniques, the variability in the copy number per cell of the most common taxonomic markers used (i.e. 16S and 18S rDNA), the incompleteness of genetic databases, which are still fed by information obtained by the isolation and cultivation approaches (Gołębiewski & Tretyn, 2020;Salmaso et al, 2020). Despite these constraints, the use of HTS techniques in the study of phytoplankton, which is just at the beginning, is contributing to revolutionize the approach we are using in the assessment of aquatic biodiversity in freshwater environments, opening the way to a next generation of investigations in phytoplankton ecology and a new improved understanding of plankton ecology.…”
Section: Culture Independent Approaches-metagenomicsmentioning
confidence: 99%